2015
DOI: 10.1155/2015/786519
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic Alterations in the Sturge-Weber Syndrome, Klippel-Trenaunay Syndrome, and the Phakomatosis Pigmentovascularis: An Independent Group of Conditions?

Abstract: The phakomatoses have been traditionally defined as a group of hereditary diseases with variable expressivity characterized by multisystem tumors with possible malignant transformation. The Sturge-Weber syndrome, Klippel-Trenaunay syndrome, and the phakomatosis pigmentovascularis have the facial port-wine stain in common. Numerous pathophysiogenetic mechanisms have been suggested such as venous dysplasia of the emissary veins in the intracranial circulation, neural crest alterations leading to alterations of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 97 publications
0
56
0
4
Order By: Relevance
“…2 Although a previous study reported that Klippel-Tr enaunay syndrome was associated with PPV type II in two of 24 cases (8.3%), most reports describe the pigmentary lesions as one or two types of dermal melanocytosis such as nevus of Ota and ectopic Mongolian spots. [2][3][4][5] In our case, the dermal melanocytosis was extensive and showed a variety in that the pigmentary lesions on his left face could be described as nevus of Ota, those on his right shoulder as nevus of Ito, and those on his right back, chest and abdomen as ectopic Mongolian spots (Fig. 1m).…”
mentioning
confidence: 60%
“…2 Although a previous study reported that Klippel-Tr enaunay syndrome was associated with PPV type II in two of 24 cases (8.3%), most reports describe the pigmentary lesions as one or two types of dermal melanocytosis such as nevus of Ota and ectopic Mongolian spots. [2][3][4][5] In our case, the dermal melanocytosis was extensive and showed a variety in that the pigmentary lesions on his left face could be described as nevus of Ota, those on his right shoulder as nevus of Ito, and those on his right back, chest and abdomen as ectopic Mongolian spots (Fig. 1m).…”
mentioning
confidence: 60%
“…Glaucoma has been cited as a common alteration associated with SWS and was one of the conditions diagnosed in this patient. Treatment with topical antiglaucoma medications is sometimes sufficient to control intraocular pressure, but not in this case, since the child was diagnosed late and was in an advanced glaucoma stage, requiring surgical intervention.…”
Section: Discussionmentioning
confidence: 83%
“…The presence of oculodermal or fundus melanocytosis encompasses a greater risk to develop melanoma. Iris mammillations can also be found, sometimes mimicking Lisch nodules typical of neurofibromatosis type 1 12. Congenital or acquired glaucoma is another condition to be aware, since intraocular pressure is increased due to ocular melanocytosis and nevus flammeus, when it appears in the ocular region 13…”
Section: Discussionmentioning
confidence: 99%